The Influence of Spiritual Care with Callista Roy's Adaptation Theory Approach on Serotonin Levels in Ischemic Stroke Patients - Nurahman Hendra Kusuma, Aria; Pudjonarko , Dwi; Sujianto , Untung (Poltekkes Kemenkes Surakarta, 2024)
Background: Ischemic stroke causes physical disability, which can result in an inability to adapt, causing a 72% decrease in serotonin. Decreased serotonin can cause mood changes that adversely impact stroke outcomes. The aim of this research is to determine the effect of spiritual care using Callista Roy's adaptation theory approach on serotonin levels in Ischemic Stroke Patients. Methods: The type of research is quasi-experimental with a pretest-posttest control group design. The population of the study was outpatients of ischemic stroke patients at Dr. Moewardi Hospital. The sample size was 60 respondents consisting of 30 respondents in the control group and 30 respondents in the intervention group. The intervention group was given a spiritual care intervention by the researcher consisting of 5 sessions each meeting with a duration of 30 minutes. The spiritual care intervention was given once a week 12 times for 3 months and the control group was given standard spiritual therapy by the outpatient nurse at RSUD Dr. Moewardi Surakarta. Serotonin examination using ELISA kit. Data analysis using independent sample t-test. Results: There is an influence of spiritual care with the Callista Roy theory approach on the serotonin levels of ischemic stroke patients with a significance of 0.001 (p value <0.05). Conclusion: Spiritual care interventions with Callista Roy's theoretical approach have a significant influence on improving serotonin levels in ischemic stroke patients, which can reduce anxiety. It is recommended that ischemic stroke patients be given spiritual care 12 times for 3 months.